2018
DOI: 10.1093/ajcp/aqx160
|View full text |Cite
|
Sign up to set email alerts
|

Dual Stain With SATB2 and CK20/Villin Is Useful to Distinguish Colorectal Carcinomas From Other Tumors

Abstract: SATB2 dual stain shows the greatest potential clinical utility in identifying CRC and is superior to CDX2 dual stain. More important, SATB2 dual stain could be helpful for specimens with limited tissues or those having a nonclassic staining pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 20 publications
2
25
0
2
Order By: Relevance
“…But it is not a good marker for diagnosis of upper GI origin (13, 19, 26). Villin was positive in our upper and lower GI origin malignancies, Previous studies showed a high positive rate range from 75% to more than 90% in colorectal carcinomas (especially in well differentiated cases) but lower rates in upper GI tumors (1,14,20,21,22). Although it is noteworthy to mention that villin expression is not limited to GI malignancies.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…But it is not a good marker for diagnosis of upper GI origin (13, 19, 26). Villin was positive in our upper and lower GI origin malignancies, Previous studies showed a high positive rate range from 75% to more than 90% in colorectal carcinomas (especially in well differentiated cases) but lower rates in upper GI tumors (1,14,20,21,22). Although it is noteworthy to mention that villin expression is not limited to GI malignancies.…”
Section: Discussionsupporting
confidence: 43%
“…CDX2 was positive in 95.5% of cases of lower GI and 50% of upper GI origin carcinomas. Previous studies showed that CDX2 could be positive in more than 90% of colorectal cancer (1,13,14,15,16). However, Su et al and Bayrak et al showed that CDX2 is not a good predictor of the lower GI origin because it could be positive in all GI tract origin cases (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, SATB2 was introduced to the diagnostic pathology community as a potential colon cancer diagnostic marker . Subsequent work has established its role as a lower GI tract‐specific columnar marker, which is especially useful in the distinction of colon cancer from variably CDX2‐expressing oesophageal, gastric, small‐intestinal and pancreatic adenocarcinomas, and in the distinction of disseminated low‐grade appendiceal mucinous neoplasm from primary mucinous ovarian tumour . Although data are limited to one study, it has also been shown to be more sensitive than CK20 and CDX2 in medullary (undifferentiated) colon cancer, with Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…24 Finally, in a study focused on identifying sensitive and specific colon cancer diagnostic makers, Li et al reported SATB2 expression in 6% of 32 (31 pancreatic; one small intestinal) 'neuroendocrine carcinomas'. 25 Given the rarity of NECs at these anatomical sites, these almost certainly represented NETs. Table 4 summarises the results of previous studies reporting on SATB2 expression in neuroendocrine neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation